Selective activation of antioxidant resources and energy deficiency in Marinesco–Sjögren syndrome fibroblasts as an adaptive biological response to Sil1 loss - Valeria Panella; Francesca Potenza; Carla Tatone; Lorenza Speranza; Fernanda Amicarelli; Michele Sallese (Scientific Reports)
Abstract Marinesco–Sjögren syndrome (MSS) is a neuromuscular disease which presents with ataxia, muscle weakness and cataracts. This syndrome is typically caused by mutations in SIL1 gene, an ER co-chaperone that disrupts protein folding. Although it is known that accumulation of misfolded proteins in the ER profoundly affect reduction–oxidation (redox) homeostasis and energy production, the possible role of these processes in MSS was not investigated to date. In patient-derived fibroblasts, both maximal mitochondrial respiration and mitochondrial ATP production rates were diminished, while the glycolytic fraction remained unaffected. Catalase and superoxide dismutase activities were increased, while glutathione peroxidase and glutathione reductase were decreased. Oxidative damage to lipids, proteins, and DNA was comparable or even lower to that observed in control cells. Similar alterations were observed in the muscle tissue of the woozy mouse model of MSS. In conclusion, we identified a mitochondrial energy deficit and an adaptive cellular mechanism that effectively manage oxidative stress in Sil1-deficient cells.